The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17559/tv-20130428110530
|View full text |Cite
|
Sign up to set email alerts
|

Planning and analysis of mechanical assembly sequences in design engineering – Part I: The Method

Abstract: Original scientific paper The article presents theoretical notions related to assembly sequence planning in the process of elements design engineering and design for machines assembly. Basic modules of the designed method are described and shown on simple examples. The concept is based on the assumption that the method should help the engineer-constructor in specifying the best assembly sequence, taking into account the principles of design for assembly at an early stage of development of the product design. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…The Network Definition Matrix (NDM) size is initially encoded in a chromosome with data. The [17] Assembler Encoding Programme (AEP) can then change the size of the NDM using the ADDN and DELN operations (as shown in Figure 5). This method enables the NDM and, in turn, the Artificial Neural Network (ANN) to be dynamically adjusted.The ANN's existing connections are unaffected as a result of the ADDN operation's addition of new neurons to the network.…”
Section: Methodology 1 Neural Network Assumptionsmentioning
confidence: 99%
“…The Network Definition Matrix (NDM) size is initially encoded in a chromosome with data. The [17] Assembler Encoding Programme (AEP) can then change the size of the NDM using the ADDN and DELN operations (as shown in Figure 5). This method enables the NDM and, in turn, the Artificial Neural Network (ANN) to be dynamically adjusted.The ANN's existing connections are unaffected as a result of the ADDN operation's addition of new neurons to the network.…”
Section: Methodology 1 Neural Network Assumptionsmentioning
confidence: 99%
“…A practical problem in the study was a dynamic approach adjusting enterprise's policy for conforming customers' needs. Sasiadek [21] presents theoretical notions related to assembly sequence planning in the process of elements design engineering and design for machines assembly. Kostic et al [22] describes the development of assembly mate references within the Webbased Virtual Laboratory for collaborative learning in industrial design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lestan et al [27] have proposed the evolutionary optimization techniques, considered to be a Genetic Algorithm (GA) to measure the scheduling efficiency. Sasiadek [28] suggested theoretical approach for an assembly involving elements design and complex machine assembly. Govindarajalu et al [29] suggested a methodology for a piston cylinder assembly to reduce the manufacturing cost.…”
Section: Literature Reviewmentioning
confidence: 99%